Adsorption Equilibria of Butan-1-ol, Toluene and Water Vapour onto Sorbonorit 4 Activated Carbon and the Co-Adsorption of Organic Compounds and Water Vapour onto SKT Activated Carbon - Józef Nastaj; Małgorzata Chybowska (Adsorption Science & Technology)
The results of both experimental and theoretical investigations are presented. The results of experimental investigations of adsorption equilibria for the pure components butan-1-ol, toluene and water vapour onto Sorbonorit 4 activated carbon are first reported, with measurements having been undertaken using a dynamic gravimetric method. The results for butan-1-ol and toluene were correlated using the Langmuir, Freundlich, Redlich–Peterson, Toth and Dubinin–Astakhov models, while the results for water vapour were correlated using the equations of Dubinin and Serpinsky and of Barton and Barton and co-workers. A simple model enabling the prediction of the adsorption equilibria of butan-1-ol/water vapour and toluene/water vapour mixtures on SKT activated carbon is then presented. Such predictions were made on the basis of data for the pure components, with the equilibrium data for both pure components and mixtures being taken from the literature. The model, which is simple to simulate and verify using experimental data, is based on the Polanyi theory and the Dubinin–Astakhov isotherm equation. With this model, fairly good agreement was observed between predicted and experimental binary mixture adsorption data for the systems examined.